Student Response to Implementation of Moega Smart School LMS in Biology Subject - Amar Rifa’i; Dinar Setiani Setiani; Laras Amalia Alwy; Destri Ratna Ma'rifah; Much Fuad Saifuddin (PAEDAGOGIA, 2022)
This study aims to determine the response of students of SMA Muhammadiyah 3 Yogyakarta to the Moega Smart School (MSS) Learning Media in Biology Subjects. This study uses a sampling technique that is Stratified Random Sampling. The sample in this study was MIPA students from class X, XI, and XII SMA Muhammadiyah 3 Yogyakarta with a total of 25% of 174 students or 43 respondents. This research includes quantitative descriptive research. The population in this study were students at SMA Muhammadiyah 3 Yogyakarta. Respondents in this study were 43 students. Data collection techniques using a questionnaire. The questionnaire contains several aspects, including aspects of implementation, ease of access, feedback, and graphics. The type of data obtained from this research is quantitative data. Data analysis was carried out by calculating the percentage of each aspect in the questionnaire sheet. The results showed that the response of Muhammadiyah 3 Yogyakarta High School students to the Moega Smart School learning media in Biology was very positive in almost all aspects. Positive responses were obtained in the aspects of the implementation of learning. In terms of ease of access, feedback, and graphics, a very positive response was obtained.